Medication errors in community pharmacies: a systematic review of the international literature. - Maguy Saffouh El Hajj; Rayah Asiri; Andy Husband; Adam Todd (PLoS ONE)
Introduction Since the 1999 report by the Institute of Medicine (IOM) 'To Err is Human.', medication safety has become a public health concern due to its impact on preventable harm and healthcare costs. While formal systems in hospitals exist to address medication errors, there is less evidence in community pharmacies. The objective of this systematic review is to synthesise and critically appraise the international evidence about the prevalence, nature, and severity of medication errors in community pharmacies. Materials and methods A systematic review was conducted for the literature published from January 1995 to December 2023. The choice of this date range was made to include a sufficient breadth of research conducted both preceding and subsequent to the publication of the IOM report. Various databases were used, supplemented by manual searches of bibliographies and grey literature. Studies were selected through a rigorous screening process. Data extraction and quality assessment were carried out using structured tools. Narrative and descriptive synthesis was conducted by geographical regions. Results 56898 potentially eligible studies were identified, yielding 73 included studies. Most studies were conducted in Europe and Central Asia and North America with few conducted in other regions. Most studies focused on prescribing and dispensing errors, with fewer studies addressing errors in other stages of the medication use process. Variations in error rates and types were observed across regions, which made calculating a global rate of errors challenging. Very few studies assessed the severity of medication errors with the majority of these being conducted in Europe and Central Asia and North America. Risk of bias varied, with selection and identification bias being common in all regions. Conclusions This review underscores the need to assess medication safety in regions with limited pharmacy access and advocate for a standardised global reporting framework to streamline data analysis. Additionally, it implies that investigating the types and severity of medication errors is imperative. Addressing these gaps through rigorous quantitative and qualitative research could inform policy-making and implementation of strategies to enhance patient safety in community pharmacies.